LifeSTEM: An Inquiry-Driven Digital Module for Scientific Literacy in Biology Teacher Education - Iing Dwi Lestari; Evi Amelia; Rifki Survani; Desi Eka Nur Fitriana; Mila Ermila Hendriyani; Dwi Ratnasari; Ika Rifqiawati; Indah Juwita Sari (Online Learning In Educational Research (OLER), 2026)
Scientific literacy is a fundamental competency for future biology teachers, yet existing STEM-based digital learning resources rarely address the interdisciplinary demands of biology teacher education. This study developed and evaluated LifeSTEM, an integrated digital learning module that combines plant anatomy, STEM learning, inquiry-based activities, and engineering design tasks to strengthen scientific literacy among pre-service biology teachers. Guided by the ADDIE instructional design framework, the study involved needs analysis, expert validation, iterative module development, and classroom implementation with 30 pre-service biology teachers using a one-group pre-test–post-test design. Data were collected through needs assessment, expert validation, scientific literacy tests, and learner response questionnaires. The findings indicate that the LifeSTEM module achieved high content validity and was positively received by students as an engaging and accessible learning resource. Its implementation substantially enhanced scientific literacy, particularly students' ability to explain scientific phenomena, interpret scientific evidence, and apply procedural knowledge within authentic biological contexts. The integration of inquiry-oriented STEM activities with interactive digital learning promoted meaningful engagement with complex biological concepts while encouraging evidence-based reasoning. This study contributes to biology teacher education by demonstrating how integrated digital instructional design can strengthen scientific literacy through contextual and inquiry-driven STEM learning, providing a transferable framework for preparing future science teachers in technology-enhanced learning environments.